Electronic nose for odour identification - Min Thu Ya Ko Ko. (2009)
Electronic nose comprising an array of 7 sensors circuitry and data processing software are used to identify different kinds of odors of fruits. The fruit to be identified is sensed by sensing system comprising of chemical gas sensors. The captured sensor readings are sent to personal computer for data processing. MatLab programming language and Probabilistic Neural Network is used to identify the odor of the fruit. A user friendly GUI generated using MatLab will display the result. Electronic is able to identify six different types of fruits: lemon, banana, orange, grapes, tomato and apple.